The Application of Laozi's Leadership Spirit in Contemporary Higher Education - Wenyao, Pang; Mutong, Marivic B. (Future Science / FSH-PH Publications, 2025)
This paper examines the application of Laozi's leadership spirit in contemporary higher education, focusing on the practice of integrating Laozi's ideas into teaching and policies, as well as the enlightenment of Laozi's educational philosophy for teachers and students. Employing a qualitative design, an interview with two deans, 10 teacher representatives, and 6 class monitors from the School of Electrical Engineering at Shaanxi Polytechnic Institute of Industry was conducted. The study found that the school effectively integrates Laozi's